Multi-methodological approach for assessing surface faulting and paleoliquefaction history in central Italy: applicative implications for seismic microzonation studies in the Quaternary L’Aquila basin - Tallini, Marco; Maceroni, Deborah; Falcucci, Emanuela; Galadini, Fabrizio; Gori, Stefano; Guerriero, Vincenzo; Spadi, Marco; Moro, Marco; Saroli, Michele (Frontiers in Earth Science, 2025)
Surface faulting and liquefaction are two earthquake-related effects to be considered in geological hazard assessment studies, particularly in application cases involving the construction or reconstruction of strategic buildings. The first effect is connected to the coseismic rupture on surface occurring along the active and capable fault, whereas the second relates to the ground seismic shaking and occurs mostly on sandy-silty grain sized deposits with shallow water table. Here, the results of investigations carried out in the Pagliare di Sassa village, nearby L’Aquila (central Italy), are presented, with the aim of shedding light on a potentially active and capable fault previously hypothesized at a site selected for the building of a school. The acquisition of paleoseismological, geophysical and geognostic data allowed to rule out the presence of the active and capable fault in the school area and to characterize several soft sediment deformation structures, interpreted as seismites related to two earthquake-induced paleoliquefaction events. Their occurrence has been linked through ceramic and radiocarbon dating. The seismites were used to determine the likely historical earthquakes (date, seismogenic source and magnitude), which in turn helped determine their occurrence contributing to the comprehension of the seismotectonic setting of central Italy. Lastly, the assessment of these local seismic instabilities, evidenced by the case study of Pagliare di Sassa, represents a key prerequisite for best practices in land and urban planning, devoted to the building of strategic edifice, such as a school. In such cases, the application of palaeoseismological technique proves to be invaluable for mitigating the seismic risk.